2008
DOI: 10.1111/j.1445-2197.2008.04643.x
|View full text |Cite
|
Sign up to set email alerts
|

Acinic Cell Carcinoma of the Parotid Gland: Auckland Experience and Literature Review

Abstract: Acinic cell carcinoma is an uncommon malignancy of the salivary glands and as such it has been difficult to accurately delineate its natural history. The aim of this study is to assess the behaviour of acinic cell salivary cancer of the parotid gland presenting to a single head and neck surgical unit in Auckland. The study is a structured review of cases of acinic cell carcinoma of the parotid gland presenting from 2000 to 2006 to the Head and Neck Unit at Auckland Hospital, those identified from the pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Spafford et al (9) proposed a series of indications for postoperative adjunctive radiotherapy in AciCC: 1) recurrent tumor; 2) equivocal or positive margins, or evidence of tumor spillage; 3) tumor adjacent to the facial nerve; 4) deep-lobe involvement; 5) lymph node metastases; 6) extra-parotid extension; and 7) large tumors greater than 4 cm. Greig et al (22) suggested that the indications for postoperative radiotherapy used were the presence of high-grade histological features (evidence of lympho-vascular invasion and high mitotic rate), close or positive margins at initial resection and tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Spafford et al (9) proposed a series of indications for postoperative adjunctive radiotherapy in AciCC: 1) recurrent tumor; 2) equivocal or positive margins, or evidence of tumor spillage; 3) tumor adjacent to the facial nerve; 4) deep-lobe involvement; 5) lymph node metastases; 6) extra-parotid extension; and 7) large tumors greater than 4 cm. Greig et al (22) suggested that the indications for postoperative radiotherapy used were the presence of high-grade histological features (evidence of lympho-vascular invasion and high mitotic rate), close or positive margins at initial resection and tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Acinic cell carcinoma (ACC) is an uncommon malignancy of salivary gland origin. It constitutes 2.5–7% of all parotid gland tumours and about 12% of carcinomas of the parotid gland 1,2 . The vast majority of ACCs involve the parotid gland (83–88%), and only a minor subset of cases (6–7%) originates in the minor salivary glands, predominantly of the oral cavity 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to faster growth of the tumour immediately before surgery, ulceration of the surface and suspected infiltration of adjacent structures (cT4) it was decided to remove the ipsilateral cervical lymph nodes. Because of the low grade of the tumour, no lymph node metastases in the neck, clear surgical margins and advanced age, the patient did not decide on postoperative radiotherapy, although it is recommended by some authors in case of a significant locally advanced tumour [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Total parotidectomy with neck dissection for regional lymph node removal was the treatment of choice in the 1960s. Its supporters were convinced about aggressive behaviour of the tumour in spite of the lack of clinical observations confirming this speculation [12]. On the other hand, Goodwin considered tumour removal within the limits of unaffected tissues to be the most appropriate way of treatment.…”
Section: Introductionmentioning
confidence: 99%